Assessing the use of copper slags as thermal energy storage material for packed-bed systems. (15th July 2021) - Calderón-Vásquez, Ignacio; Segovia, Valentina; Cardemil, José M.; Barraza, Rodrigo
Abstract: Thermocline tanks using packed-bed of rocks have become feasible candidates for improving the performance of Concentrated Solar Power plants, enabling high operating temperatures and reduced capital costs when industrial byproducts are employed as filler materials and low-cost working fluids, being competitive against molten salts thermal storage systems. The present work assesses the potential of using copper slags in packed-bed systems as filler material. Through a thermal characterization, it is demonstrated that copper slags show similar properties to other slags proposed in the literature for thermal storage medium and better thermal capacity (1.4–1.5 J/(gK)). A heat transfer model was developed to predict the cyclic behavior of a packed-bed storage using copper slags and employed in a parametric analysis to assess the impact of storage dimensions on 1 st and 2 nd law efficiencies for different storage materials, allowing to identify several design considerations depending on tank's volume. The main findings indicate that the high thermal capacity of copper slags favors the development of a steeper thermocline, keeping a low rate of exergy loss at storage's outlet, and also higher energy density stored of 138 kWh/m 3 against 129 kWh/m 3 of other byproducts under similar storage dimensions. Highlights: Assessment of the use of copper slags as filler material in packed-bed systems. Thermal characterization of the copper slags from samples from local foundry. Copper slag shows better thermal capacitance than other industrial byproducts. Development of a 1D model for assessing the packed-bed thermal performance. Study of the impact of the aspect ratio and tank's volume on energy efficiency.